2020
DOI: 10.3390/molecules25173816
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivities of Choline Chloride-Based Deep Eutectic Solvents and Their Mixtures with Water: Measurement and Estimation

Abstract: The thermal conductivities of selected deep eutectic solvents (DESs) were determined using the modified transient plane source (MTPS) method over the temperature range from 295 K to 363 K at atmospheric pressure. The results were found to range from 0.198 W·m−1·K−1 to 0.250 W·m−1·K−1. Various empirical and thermodynamic correlations present in literature, including the group contribution method and mixing correlations, were used to model the thermal conductivities of these DES at different temperatures. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Several studies have been carried out regarding the thermophysical properties of several ILs and DES [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and both have been proved to be good dispersant media for CNTs dispersion [ 21 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out regarding the thermophysical properties of several ILs and DES [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and both have been proved to be good dispersant media for CNTs dispersion [ 21 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gautam and Seth observed that the thermal conductivities of ammonium-based DESs decreased slightly as the temperature increased. Ibrahim et al used an improved transient plane source method to measure the thermal conductivities of seven choline chloride-based DESs in the temperature range from 295 to 363 K at atmospheric pressure. The thermal conductivities decreased slightly with the increase of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they obtained temperature dependencies that follows the observed tendencies for the liquids of the present study. The influence parameters of temperature were obtained by linear fitting. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations